Modified hepaticocholecystoenterostomy technique for certain hepatobiliary and pancreatic diseases: case series report by a single surgeon - Hieu Hoc, Tran; Que Son, Tran (Journal of the Pakistan Medical Association, 2023)
Prior to this research, very few reports of hepaticocholecystoenterostomy (HCE) and its modification have been published. Two anastomoses were used to establish a biliary bypass using the gallbladder as a conduit by a senior hepato-biliary surgeon. Between 2013 and 2019, 11 patients (five men and six women) with a mean age of 61.7 ± 15.7 (range, 31 – 85) years were seen. Disease indications included periampullary malignant tumours of Vater (7 cases), chronic pancreatitis (1 patient), cystic pancreatic head tumours (2 patients), and choledochal cysts (1 patient). Pancreaticoduodenectomy, bypass, cholangiocarcinoma, and choledochal cystectomy were performed on 4, 4, 2, and 1 patients, respectively. Followup showed no jaundice at all with no recurrent biliary obstruction. ---Continue